Cytotoxicity study of pyrazole derivatives - Nusrat Binta Ahasan and Md. Rabiul Islam (Bangladesh Pharmacological Society, 2007)
Pyrazolone heterocyclic compound, 3-methyl-1-phenyl-2-pyrazoline-5-one 2(a) was synthesized by condensation reaction between ethyl acetoacetate and phenyl hydrazine and was converted into their corresponding heterocyclic derivatives 2(b) to 2(f2). Their cytotoxicity effects were measured by brine shrimp lethality bioassay. Among them the compounds 2(b), 2(f1), and 2(f2) were highly active according to IC50 values 19.50, 19.50 and 20 ppm respectively. The rest of compounds 2(a), 2(c), 2(d1), and 2(d2) having IC50 values 38, 33.50, 37.50, 36, 37.50 and 36 ppm in that order, were moderately active.